An Axiomatization of the Banzhaf Index to Measure Influence in Qualitative Comparative Analysis - Haake, Claus-Jochen; Schneider, Martin (International Journal of Game Theory)
The Banzhaf power index can be used to quantify the explanatory power of single conditions in a configurational analysis that aims at identifying whether combinations of conditions are sufficient for an outcome. The latter method is an integral part of the Qualitative Comparative Analysis (QCA) approach. It is widely used in the literature, e.g., in the field of International Management. Haake and Schneider (2023) give a rigorous description of the connection between the empirical and game theoretic modeling. To justify that the Banzhaf index is an appropriate tool to measure the influence of a condition, this paper discusses a novel axiomatization of the Banzhaf index that uses axioms that are directly linked to the QCA methodology. As a side result, we demonstrate that in our model the Banzhaf index can be reinterpreted as an average of Shapley-Shubik indices.
Keywords: Banzhaf index; axiomatization; QCA; explanatory power

Life-cycle health effects of compulsory schooling - Hollenbach, Johannes; Schmitz, Hendrik; Tawiah, Beatrice Baaba (The European Journal of Health Economics)
Abstract We study the effect of education on health (hospital stays, number of diagnosed conditions, poor or bad self-rated health, and body mass index) over the life cycle, using German compulsory schooling reforms as a source of exogenous variation. Our results show clear correlations between educational attainment and better health across all age groups (30 to 74). However, we do not find causal relationships between additional schooling and health or health care utilization, neither earlier nor later in life. A simulated ex-post power analysis shows that this is not due to a lack of statistical power. One reason for the absence of effects may be that the studied compulsory schooling reforms succeeded in raising the educational attainment of the target group - individuals at the lowest educational margin - but did not lead to healthier employment opportunities.

Gene-environment interactions with essential heterogeneity - Hollenbach, Johannes; Schmitz, Hendrik; Westphal, Matthias (The Economic Journal)
Abstract We study how gene-environment interactions between education and genetic endowments affect cognition in old age and use this setting to show that – even with a valid instrument – two-stage least squares (2SLS) estimates of interaction effects can be far away from the true effect. This is the case when treatment effects are heterogeneous and compliance to the instrument depends on the interaction variable. We suggest estimating marginal treatment effects to address this problem. Our estimation results show complementarities between education and genetic predisposition in determining later-life memory. The marginal treatment effect estimates suggest substantially larger gene-environment interactions than the 2SLS estimates.

Bildung in der Jugend hält das Gehirn jung - Schmitz, Hendrik; Matthias, Westphal (Wirtschaftspsychologie heute)

A Note on the Size Reduction Reform in the German Parliament: A Game Theoretic Analysis of Power Indices - Duman, Papatya; Haake, Claus-Jochen (Review of Economics)
Abstract We investigate whether the recently approved reforms of the apportionment of parliamentary seats to parties in the German Bundestag affects the parties’ political influence measured by power indices. We find that under neither reform the underlying simple game, which describes the possibilities to form governments, remains unchanged and as a result the Shapley-Shubik and the Banzhaf index are unaltered. As a consequence, the major change resulting from the reforms is the reduction of the Bundestag’s size to 630 seats.
Keywords: Bundestag reform; Banzhaf power index; Shapley-Shubik power index

Education as a Moderator of Genetic Mortality Risk - Schmitz, Hendrik; Nguyen, Thao Le

Microfoundations of Absorptive Capacity as Revealed by Inventor Deaths - Balsmeier, Benjamin; Fleming, Lee; Lück, Sonja (Management Science)
We return to the theoretical foundations of absorptive capacity and test the idea that personal experience in a field makes it easier for a firm’s inventors to recognize and build upon knowledge in that field from other local firms. We propose a new empirical model of localized knowledge diffusion, which (1) measures a firm’s absorptive capacity by its inventors’ prior experience in a field, (2) uses a death instrument to exogenously vary the availability of knowledge of the same collaborative patent in different regions, and (3) estimates the difference in citation likelihood from all subsequent inventors across both regions as a function of a potentially citing inventor’s prior experience in the field. Consistent with the original theory of absorptive capacity, firms whose inventors have prior experience in a field are more likely to use locally available interpersonal knowledge from other firms; furthermore, this effect declines monotonically with distance. Although the effects strengthen for more recent experience and multidisciplinary knowledge, the greatest benefits accrue to firms in the interaction—those whose inventors have more recent experience and that seek to absorb multidisciplinary knowledge. Interpersonal absorptive capacity within firms does not appear to localize. This paper was accepted by Anita McGahan, business strategy. Funding: The authors acknowledge financial support from the Alfred P. Sloan Foundation and the National Science Foundation [Grant 1360228]. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2024.06147 .

The Effect of Compulsory Schooling on Vaccination Against COVID - Monsees, Daniel; Schmitz, Hendrik (Health Economics)
ABSTRACT We study the effect of education on vaccination against COVID in Germany in a sample of individuals above the age of 60. In ordinary least squares regressions, we find that, in this age group, one more year of education goes along with a 0.7 percentage point increase in the likelihood to get a COVID vaccination. In two stage least squares regressions where changes in compulsory schooling laws are used as exogenous variation for education, the effect of an additional year of education is estimated to be zero. The results hold for the compliers to the policy change which are older individuals at the lowest margin of education.

The Economics of Ideologies - Gries, Thomas; Burs, Carina; Müller, Veronika
Many of the major international and intrastate crises and conflicts, but also the threat to democratic principles, are driven by belief systems and ideologies. They fuel political polarization, which is particularly evident in the battleground of social media. Nevertheless, we hardly pay attention to ideologies, their narratives, functions and organizations in economic theory today. Ideologies as “non-rational beliefs” seem incompatible with rationality in economic models. Therefore, the book examines the role of ideologies and belief systems in individual decision-making behavior from an economic and rational perspective. Due to the fact that people have incomplete information, belief systems and ideologies fulfill a number of important functions. While ideologies themselves serve psychological needs, they are used as a cognitive framework for rational decision-making once they have been adopted through a Bayesian learning process. They influence decisions in a wide range of areas, from consumption and work to politics. This is where the role of ideological organizations becomes important, because they determine the ideological direction of the narratives and their dissemination. Thus, ideologies give a normative direction, for better or for worse. The “quality” of ideological leadership can be evaluated normatively on the basis of principles such as individual sovereignty and human dignity. A democratic discourse requires an information and communication system that enables an evaluation of precisely these ideologies, free from resource and information power.

Science knowledge localizes - Balsmeier, Benjamin; Lück, Sonja; Fleming, Lee (Research Policy)

Playing games with QCA: Measuring the explanatory power of single conditions with the Banzhaf index - Haake, Claus-Jochen; Schneider, Martin (Journal of International Management)
Qualitative comparative analysis (QCA) enables researchers in international management to better understand how the impact of a single explanatory factor depends on the context of other factors. But the analytical toolbox of QCA does not include a parameter for the explanatory power of a single explanatory factor or “condition”. In this paper, we therefore reinterpret the Banzhaf power index, originally developed in cooperative game theory, to establish a goodness-of-fit parameter in QCA. The relative Banzhaf index we suggest measures the explanatory power of one condition averaged across all sufficient combinations of conditions. The paper argues that the index is especially informative in three situations that are all salient in international management and call for a context-sensitive analysis of single conditions, namely substantial limited diversity in the data, the emergence of strong INUS conditions in the analysis, and theorizing with contingency factors. The paper derives the properties of the relative Banzhaf index in QCA, demonstrates how the index can be computed easily from a rudimentary truth table, and explores its insights by revisiting selected papers in international management that apply fuzzy-set QCA. It finally suggests a three-step procedure for utilizing the relative Banzhaf index when the causal structure involves both contingency effects and configurational causation.
Keywords: Qualitative comparative analysis; Banzhaf power index; causality; explanatory power

An early indicator for anomalous stock market performance - Fritz, Marlon; Gries, Thomas; Wiechers, Lukas (Quantitative Finance)
We propose an indicator for detecting anomalous stock market valuation in real time such that market participants receive timely signals so as to be able to take stabilizing action. Unlike existing approaches, our anomaly indicator introduces three methodological novelties. First, we use an endogenous, purely data-driven, nonparametric trend identification method to separate long-term market movements from more short-term ones. Second, we apply SETAR models that allow for asymmetric expansions and contractions around the long-term trend and find systematic stock price cycles. Third, we implement these findings in our indicator and conduct real-time market forecasts, which have so far been neglected in the literature. Applications of our indicator using monthly S&P 500 stock data from 1970 to the end of 2022 show that short-term anomalous market movements can be identified in real time up to one year ahead. We predict all major anomalies, including the 1987 Bubble and the initial phase of the Financial Crisis that began in 2007. In total, our anomaly indicator identifies more than 80% of all – even minor – anomalous episodes. Thus, smoothing market exaggerations through early signaling seems possible.
Keywords: General Economics; Econometrics and Finance; Finance

Artificial Intelligence - Naudé, Wim; Gries, Thomas; Dimitri, Nicola
Is Artificial Intelligence a more significant invention than electricity? Will it result in explosive economic growth and unimaginable wealth for all, or will it cause the extinction of all humans? Artificial Intelligence: Economic Perspectives and Models provides a sober analysis of these questions from an economics perspective. It argues that to better understand the impact of AI on economic outcomes, we must fundamentally change the way we think about AI in relation to models of economic growth. It describes the progress that has been made so far and offers two ways in which current modelling can be improved: firstly, to incorporate the nature of AI as providing abilities that complement and/or substitute for labour, and secondly, to consider demand-side constraints. Outlining the decision-theory basis of both AI and economics, this book shows how this, and the incorporation of AI into economic models, can provide useful tools for safe, human-centered AI.

The Effects of Norms on Environmental Behavior - Dannenberg, Astrid; Gutsche, Gunnar; Batzke, Marlene C. L.; Christens, Sven; Engler, Daniel; Mankat, Fabian; Möller, Sophia; Weingärtner, Eva; Ernst, Andreas; Lumkowsky, Marcel; von Wangenheim, Georg; Hornung, Gerrit; et al. (Review of Environmental Economics and Policy)

The individual and ecological characteristics of parental COVID-19 vaccination decisions - Hörnig, Lukas; Schaffner, Sandra; Schmitz, Hendrik (Scientific Reports)
Abstract Vaccination is a highly effective method to prevent the spread of COVID-19 and mitigate severe disease. In Germany, adult vaccination rates are relatively high at 85.5%, but rates are significantly lower for adolescents (69.6%) and children (20.0%). This discrepancy indicates that not all vaccinated parents choose to vaccinate their children. Analyzing data from a January 2022 online survey of 1,819 parents with children and adolescents, we explore the socio-economic factors influencing parents’ willingness to vaccinate themselves and their children. Our results show that individuals who vote for either side of the political extremes are less likely to vaccinate their children. This pattern is particularly strong for voters on the far right. In addition, we find that better educated parents are more likely to vaccinate both themselves and their children. Parents who vaccinate both themselves and their children demonstrate greater confidence in the vaccine’s effectiveness, while those who vaccinate only themselves are often motivated by a desire to regain personal freedoms. These insights highlight the need for targeted public health strategies to address specific concerns and improve vaccination rates among children and adolescents.

Regional variations in vaccination against COVID-19 in Germany - Bade, Verena; Schmitz, Hendrik; Tawiah, Beatrice Baaba (PLOS ONE)
Vaccination willingness against COVID-19 is generally perceived as low. Moreover, there is large heterogeneity across and within countries. As a whole, Germany has average vaccination rates compared to other industrialized countries. However, vaccination rates in the 16 different German federal states differ by more than 20 percentage points. We describe variation in vaccination rates on the level of the 400 German counties using data on all vaccinations carried out until December 2022. Around 52-72% of that variation can be explained by regional differences in demographic characteristics, housing, education and political party preferences. We find indications that the remaining part may be due to differences in soft factors such as risk aversion, trust in the German government, trust in science, and beliefs in conspiracy theories regarding the origins of the Corona virus. We conclude that improving the trust in science and the fight against conspiracy theories may possibly be effective tools to improve vaccination rates and effectively fight pandemics.

Social norms and individual climate protection activities: A survey experiment for Germany - Engler, Daniel; Gutsche, Gunnar; Simixhiu, Amantia; Ziegler, Andreas (Energy Economics)

Forecasting economic growth by combining local linear and standard approaches - Fritz, Marlon; Forstinger, Sarah; Feng, Yuanhua; Gries, Thomas (Journal of Applied Statistics)

Energy and sustainability: a balanced energy transition strategy - Kolosok, Svitlana; Myroshnychenko, Iuliia; Gries, Thomas (The Elgar Companion to Energy and Sustainability)

Ideology and the Microfoundations of Conflict - Müller, Veronika; Gries, Thomas
Abstract This book combines theoretical and empirical research across various academic disciplines, including economics, psychology, neuroscience, philosophy, and political science, to describe why individuals adopt political ideologies and how this choice can potentially exacerbate conflict and violence. Ideology is particularly important to conflict. Data on intra- and international conflict shows that the number of ideologically driven conflicts has increased tremendously in recent decades. Although some researchers have started to investigate extensively the link between ideology and conflict, they struggle to find holistic explanations through which ideologies might shape conflict. This book addresses this effort by providing an interrelated multidisciplinary framework to explain the multidimensional functions of ideology. It illustrates that ideologies are not only capable of shaping conflictual behavior or mobilizing political actors, but also of addressing human needs, desires, and preferences. Hence, this book seeks to explain how individuals adopt ideologies that match their underlying needs and preferences; that ideologies have the capacity to reconcile deprived psychological human needs; and that radical groups and organizations use ideologies to recruit individuals and pursue their objectives. To understand these relationships better and to apply the theoretical background to real-world situations, we include real-life cases that describe how depriving individuals of resources that satisfy their underlying needs and preferences can lead them to adopt particular ideologies that are disseminated by radical groups or organizations. These radical groups or organizations then make decisions, which can potentially lead to conflict onset and continuous long-term struggles.